The Importance Of Biophysical Methods In Dentistry - Akhrorov Ma’ruf Nasimjonovich (Academia One Publishing, 2025)
The shape and relief of the alveolar ridge play a crucial practical role in the successful use of dental prostheses. For effective prosthodontic treatment, alveolar ridges with a truncated cone or semi-oval shape are considered more favorable. In such configurations, masticatory pressure is distributed over a limited area at the ridge crest and gradually transferred to the broader base of the alveolar process. In contrast, triangular, sharp-edged, or irregularly shaped ridges are highly unfavorable, as they often lead to trauma of the overlying mucosal tissues. Patients with such ridge forms frequently complain of persistent pain and discomfort during prosthesis wear
Keywords: Palpation; Percussion; Stomatoscopy